Konvergensi Pendapatan Perkapita: Studi Kasus Antar Kabupaten di Indonesia pada Era Otonomi Daerah - Pebriani, Komang Ayuk; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 3, Maret 2013 (pp. 119-172), 2013)
Many policies have been employed in order to incrase the standart of living; one of them is decentralization. This research tries to test the existence of income percapita convergence among the Kabupaten/Kota in Indonesia during the decentralization era (1999 to 2010). The empirical model that we use to test the convergence was the OLS procedure based on Baumol (1986), De Long (1988), Varblane and Vahter (2005 : 21-25), and Monfort (2008), by using cross section data from 187 Kabupaten/kota in Indonesia. The research result show that the 2010 percapita GDRP variabel has positively and significantly effect toward the 2010 percapita GDRP and 1999 percapita GDRP difference, this result was contradictive againts the conergence hypothesis, hence, we can infer that no convergence, but we found divergence condition. The same result also shows by the Jarak variabel, which not support the convergence hypothesis. In general, we can infer that the decentralization policy in Indonesia has not yet success to decrease the income percapita gap among Kabupaten/kota in Indonesia during the decentralization era.
Keywords: inequality; convergence; divergence; decentralization